2011 Triennial Surveillance Review : External Study. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
External study prepared by Stephen Pickford, former IMF/World Bank Executive Director for the United Kingdom and former Managing Director of International and Europe at H.M. Treasury and G-20 Finance Deputy, United Kingdom: Surveillance (both bilateral and multilateral) is a key instrument for the Fund's crisis prevention role, analyzing economic developments and policies at national, regional and global levels. It also identifies risks and vulnerabilities, and forms the main basis for the Fund's discussions with policy-makers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country; Fund; Policy; PP; Product; Afghanistan, Islamic Republic of